Retorno em organizações hospitalares: abordagem crítica das decisões de investimentos com base em estudo de caso - Araujo Junior, Edalmo Pacifico de (2010)
Return in Hospital Organizations: a Critical Approach to the Investment Decisions Based on a Case Study. This study has the objective of showing how effective hospital institutions have been in their investment decisions, based on operational results (ROI). It intends to specifically investigate if Private Hospitals inserted in competitive markets which care exclusively for private patients are more effective in allocating investments than Private Hospitals which care for patients coming from the Sistema Único de Saúde (SUS) and are not inserted in a competitive environment. The methodology used was a multicased one, characterized as a qualitative and exploratory research of descriptive type. It involved two distinct groups: one formed by two private hospitals in the city of São Paulo inserted in a competitive market; and the other formed by two private hospitals which care for patients from SUS not submitted to competitive markets. The data were collected with the use of managerial reports and a questionnaire composed of 15 questions. The intention is to identify the correlation of investments made by the hospitals and their economical results, as well as their production amount. It was verified that the hospitals which work with SUS and are not inserted in a competitive market are effective in generating economical return due to the investments used; however, this fact does not occur in private hospitals which receive private patients and are inserted in the market. It was observed that hospitals which work with SUS are effective in using investments, in relation to the dislocating of less profitable to more profitable services, and that they generate more health to the population, opposite to the hospitals not related to SUS, which did not present a relation between investments and service offer at all